Immigrants at new destinations: How they fare and why - Anabela Carneiro; Natércia Fortuna; José Varej\~ao (Institute for the Study of Labor (IZA), 2010)
Using matched employer-employee data, we identify the determinants of immigrants' earnings in the Portuguese labor market. Results previously reported for countries with a long tradition of hosting migrants are also valid in a new destination country. Two-thirds of the gap is attributable to match-specific and employer characteristics. Occupational downgrading and segregation into low-wage workplaces are two major causes behind the wage gap.
Keywords: J15; J24; J61; 330; Immigrants' earnings; workplace concentration of immigrants; matched employer-employee data; Migranten; Lohndifferenzierung; Einkommen; Überqualifikation; Arbeitsmarkt; Matching; Schätzung; Portugal